INTERAKSI SENI DAN RUANG PUBLIK: RELEVANSI MURAL TUGU TUNAS DALAM PENDIDIKAN SENI - Sukma, Afra (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2025)
This research is motivated by the role of murals at Tugu Tunas as a visual communication medium in public spaces, which is unique because it is applied to the surface of a monument, differing from most murals that are usually found on building walls. This study aims to analyze visual communication and its relevance to art education in the murals at Tugu Tunas, Semarang City. The method used is qualitative with a phenomenological approach. Data was collected through field observations and interviews with various informants and validated through three stages of phenomenological validation.The results show that the mural at Tugu Tunas aims to visually represent Semarang's local culture. Through a semiotic study, the message conveyed in this mural aligns with the concept translated from government and artist ideas. The artists successfully translated cultural symbols accurately, allowing the public to understand their meaning. However, communication disturbances were found, such as the limited visual field of the monument and the public's lack of understanding of the symbols used. Thus, the mural at Tugu Tunas not only holds aesthetic value but also functions as an educational medium that provides artistic insights and aesthetic experiences to the community.